HPTLC analysis of Fumaria parviflora (Lam.) methanolic extract of whole plant - Anjali Bhargava; Pragya Shrivastava; Anita Tilwari (SpringerOpen, 2021)
Abstract Background Fumaria parviflora (Lam.), commonly known as "fine-leaved fumitory," is well known for its therapeutic properties in the Indian traditional medicinal system. The presence of important bioactive compounds in plants makes them pharmacologically valuable. Therefore, in the present study, the high-performance thin layer chromatography (HPTLC) analysis of Fumaria parviflora (whole plant) methanolic extract was performed for its phytochemical profiling. Results The HPTLC densitometric analysis of the methanolic extract of Fumaria parviflora (whole plant) was carried out using CAMAG HPTLC system, and the results were obtained in the form of chromatograms (scanned at the wavelength of 254 nm and 366 nm) representing several peaks. The phytochemical profile of the plant was determined and presented in the tables showing the total number of peaks, peak heights, peak area, percent area, and Rf values. Conclusion The study concluded that F. parviflora methanolic extract of the whole plant contains a rich variety of phytochemicals which might be accountable for its therapeutic value and thus justifies its traditional use in India.